Facile Modification of Propiolated Castor Oil via Nucleophilic Thiol-Yne Click Reactions - ÇAKMAKÇI, EMRAH (My University, 2024)
The combination of modern click protocols and bio-based building blocks is a great step toward energy-efficient, and sustainable polymer production. Herein, thiol-Michael addition (thiol-yne) reactions from the toolbox of click chemistry protocols are chosen and propiolated castor oil (PCO) is used, a vegetable oil derivative, as the bio-based building block for the facile functionalization of PCO with various thiols. In addition to the functionalization of PCO, hyperbranched and crosslinked polymers are also prepared. The thiol-yne click functionalization reactions of the PCO are conducted at room temperature within 5 min and in the presence of an organic catalyst. The yields are found to change between 80% and 99% depending on the type of the thiol compound. The effect of various organic catalysts is investigated, and 1,8-diazabicyclo(5.4.0)undec-7-ene (DBU) is found to be the most effective catalyst for the thiol-yne modification reactions. The hyperbranched polymer reaches 23.8 kDa (Mw) within 5 min. The findings of this paper open up new horizons for polymer researchers who work in the field of sustainable polymers and click chemistry and the presented idea here is appealing because it offers a potential strategy for fast, reliable, modular, and functional macromolecule preparation from renewable vegetable oils.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; KİMYA, FİZİKSEL; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; PHYSICS; POLYMER SCIENCE; CHEMISTRY, PHYSICAL; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; PHYSICS, CONDENSED MATTER; Yoğun Madde Fiziği; Fizik Bilimleri; Fiziksel ve Teorik Kimya; Polimerler ve Plastikler; Organik Kimya; Malzeme Kimyası; Condensed Matter Physics; Physical Sciences; Physical and Theoretical Chemistry; Polymers and Plastics; Organic Chemistry; Materials Chemistry; activated alkyne; castor oil; hyperbranched polymers; thiol-michael click reactions